Dephasing Mechanisms of Topologically Protected 2D Surface Carriers in Sputtered SnTe Thin Films - Beryani Nezafat, Negin; Bhattacharya, Ahana; Izadi, Sepideh; Ennen, Inga; Wortmann, Martin; Schnatmann, Lauritz; Solaymani, Shahram; Kulesza, Sławomir; Bramowicz, Miroslaw; Westphal, Michael; Biedinger, Jan; Rott, Karsten; et al. (Nano letters, 2025)
Tin telluride (SnTe), a topological crystalline insulator, features two-dimensional (2D) surface charge carriers with topological protection and 3D bulk charge carriers. The outstanding electronic properties of the 2D carriers are often obscured in experiments due to their relatively low number. We address this by using nanocrystalline sputtered SnTe thin films deposited at room temperature, which increase the proportion of 2D carriers. Here, we correlate the structural and electronic parameters and investigate the dephasing mechanisms of these 2D electrons. The dephasing mechanisms vary from quasi-1D electron–electron interactions in the thinnest film studied to 2D electron–electron interactions and finally to electron–phonon interactions in thicker films. Using THz time domain spectroscopy, we measured the scattering rates of the 2D charge carriers and found excellent agreement with the Hikami-Larkin-Nagaoka (HLN) model.